2018
DOI: 10.1021/acscatal.8b02882
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Alkyl Hydroperoxide and Acyl Hydroperoxide Disproportionation by a Nonheme Iron Complex

Abstract: Alkyl hydroperoxides are commonly used as terminal oxidants because they are generally acknowledged to be stable towards disproportionation compared with H2O2. We show that alkylperoxide disproportionation is effectively catalyzed by the [Fe(tpena)] 2+ (tpena = N,N,N'tris(2-pyridylmethyl)ethylendiamine-N'-acetate). A peroxidase type mechanism, in other words, involvement of iron(IV)oxo species, is consistent with the rates and product distribution. Accordingly, O2 and tert-butanol and cumyl alcohol are concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Given that the background • OH radical concentration will be the same in all reactions, and presuming that the iron hydroperoxides are not active as the direct oxidants, 60,61 then it can be concluded that [Fe IV O(Htpena)] 2+ is the most potent iron(IV) oxo species in this series and is consistent with the oxidation of cyclohexanol in water using [Fe IV O(Htpena)] 2+ generated by electroactivation where no • OH radicals are present. 50 69 We can conclude from all the observations that the latent iron(IV)oxo complex of tpena is more rapidly available, in higher concentrations, in comparison with the tpen-and tpenOsupported systems in the presence of H 2 O 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…Given that the background • OH radical concentration will be the same in all reactions, and presuming that the iron hydroperoxides are not active as the direct oxidants, 60,61 then it can be concluded that [Fe IV O(Htpena)] 2+ is the most potent iron(IV) oxo species in this series and is consistent with the oxidation of cyclohexanol in water using [Fe IV O(Htpena)] 2+ generated by electroactivation where no • OH radicals are present. 50 69 We can conclude from all the observations that the latent iron(IV)oxo complex of tpena is more rapidly available, in higher concentrations, in comparison with the tpen-and tpenOsupported systems in the presence of H 2 O 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…Rate constants of 1.2 × 10 −3 and 4 × 10 −4 M −1 s −1 were deduced respectively for the decay of [Fe IV O(tpena)] + at pH 6−7 and [Fe IV O(Htpena)] 2+ pH 3−4 in buffered water. 60 This was ascribed to slow water oxidation. While our work shows that [Fe IV O(Htpena)] 2+ is the most potent aqueous iron(IV) oxo complex for C−H oxidation in the present series, slow background water oxidation might marginally compromise this activity, when C−H substrates are limited.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Hence, LAOOH would readily be decomposed by CoPor into LAO· through O–O bond homolytic cleavage. , With respect to the strongest relative abundance of LAOH in the presence of CoPor (Figure B), LAOOH probably converted into LAOH via LAO· through H-abstraction. In addition, LAO· would likely to be converted into the corresponding fatty aldehyde through homolytic β-scission. …”
Section: Resultsmentioning
confidence: 99%